Relationship between left ventrikular dimensions and functional and maximal oxygen uptake in young swimmers - Madeira, R.; Trabulo, M.; Alves, F.; Gomes Pereira, J. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to analyse the relationship between left ventricular (LV) dimensions/function and maximal oxygen uptake (VO2max) in young swimmers. Twelve well trained swimmers (15.9±0.2years; 64.2±6.8kg; 1.75±0.06m) underwent anthropometric measurements, resting M-mode/Doppler echocardiography and a treadmill running protocol. Allometric scaling of heart morphological characteristics by body dimensions was performed. Heart size was highly correlated with VO2max and end-diastolic LV internal chamber dimension was the main determinant factor. Ejection fraction and VO2max were uncorrelated suggesting that the systolic function at rest does not reflect cardiac function at maximal exercise. Conclusion is that VO2max determined by a non-specific maximal protocol can be an indicator of cardiac adaptations to aerobic exercise.